Some reflections on In Dubio Pro Tributario principle - Dowgier, Rafał (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
As of the beginning of 2016 the principle of resolving possible interpretation doubts for the benefit of a taxpayer (in dubio pro tributario) was introduced to the Polish legal order. This rule was upgraded to the tax law principle expressed directly in Art. 2a of the Act of 27 August 1997 – Tax Ordinance. Such a decision of the legislator resulted from a prior referendum, wherein nearly 95% of voters supported the introduction of this principle, perceiving it, apparently, as an instrument that would enhance the practice of tax law application by tax authorities. After several years, it can be assumed that these hopes have not been fulfilled since this principle has not been applied more widely in the practice so far. The purpose of this study is to present both the very essence of in dubio pro tributario principle and experiences concerning its application in recent years, with a particular focus on the rulings issued thereon by administrative courts and Constitutional Tribunal.

Z początkiem 2016 r. do polskiego porządku prawnego wprowadzono zasadę rozstrzygania wątpliwości na korzyść podatnika (in dubio pro tributario). Regułę tę podniesiono do rangi zasady prawa podatkowego wyartykułowanej wprost w art. 2a ustawy z dnia 27 sierpnia 1997 r. – Ordynacja podatkowa. Ten ruch ustawodawcy był wynikiem uprzedniego referendum, w którym prawie 95% głosujących opowiedziało się za wprowadzeniem tej zasady, dostrzegając w niej zapewne narzędzie, które przyczyni się do polepszenia praktyki stosowania prawa podatkowego przez organy podatkowe. Po kilku latach można stwierdzić, iż nadzieje te nie zostały zrealizowane. W praktyce bowiem przedmiotowa zasada jak na razie nie znajduje szerszego zastosowania. Celem opracowania jest przedstawienie zarówno samej istoty zasady in dubio pro tributario, jak i doświadczeń na tle jej stosowania na przestrzeni ostatnich lat, ze szczególnym uwzględnieniem wydanych w tym zakresie orzeczeń sądów administracyjnych oraz Trybunału Konstytucyjnego.
Keywords: tax; tax law; interpretation of law; tax law principles; podatki; prawo podatkowe; wykładnia prawa; zasady prawa podatkowego